Fibrotic-like changes in degenerate human intervertebral discs revealed by quantitative proteomic analysis. Issue 3 (March 2016) - Yee, A.; Lam, M.P.Y.; Tam, V.; Chan, W.C.W.; Chu, I.K.; Cheah, K.S.E.; Cheung, K.M.C.; Chan, D.
Summary: Objective: Intervertebral disc degeneration (IDD) can lead to symptomatic conditions including sciatica and back pain. The purpose of this study is to understand the extracellular matrix (ECM) changes in disc biology through comparative proteomic analysis of degenerated and non-degenerated human intervertebral disc (IVD) tissues of different ages. Design: Seven non-degenerated (11–46 years of age) and seven degenerated (16–53 years of age) annulus fibrosus (AF) and nucleus pulposus (NP) samples were used. Proteins were extracted using guanidine hydrochloride, separated from large proteoglycans (PGs) by caesium chloride (CsCl) density gradient ultracentrifugation, and identified using liquid chromatography (LC) coupled with tandem mass spectrometry (MS/MS). For quantitative comparison, proteins were labeled with iTRAQ reagents. Collagen fibrils in the NP were assessed using scanning electron microscopy (SEM). Results: In the AF, quantitative analysis revealed increased levels of HTRA1, COMP and CILP in degeneration when compared with samples from older individuals. Fibronectin showed increment with age and degeneration. In the NP, more CILP and CILP2 were present in degenerated samples of younger individuals. Reduced protein solubility was observed in degenerated and older non-degenerated samples correlated with an accumulation of type I collagen in the insoluble fibers. Characterization of collagen fibrils in the NP revealed smaller mean fibril diameters and decreased porosity in the degenerated samples. Conclusions: Our study identified distinct matrix changes associated with aging and degeneration in the intervertebral discs (IVDs). The nature of the ECM changes, together with observed decreased in solubility and changes in fibril diameter is consistent with a fibrotic-like environment.